The Practice of Ideological Mobilisation of Power by the Mayor of Jayapura in the 2025 Papua Governor Election: A Critical Discourse Analysis - Robert Masreng (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
The 2025 Papua Gubernatorial Election represents a crucial moment in the dynamics of local democracy in Papua. This study investigates the ideological practices of power mobilization carried out by the Acting Mayor of Jayapura and examines how discourse is strategically employed to influence electoral outcomes. The objectives of this research are to identify forms of power mobilization, analyze discourse strategies used to shape public opinion, and examine power relations between local elites and provincial political structures. This research employed a qualitative descriptive approach using Norman Fairclough’s Critical Discourse Analysis (CDA) framework. The data consisted of transcripts of conversations between the Acting Mayor of Jayapura and district heads and village officials. Data were analyzed through three dimensions: text, discursive practice, and social practice, supported by verstehen and interpretive methods. The findings reveal that power mobilization was conducted through financial distribution, door-to-door voter mobilization, transportation arrangements for voters, manipulation of voter invitations and identity documents, and the deployment of witnesses and supervisors to secure electoral support. Furthermore, discourse strategies included the use of bodily metaphors and symbolic gestures, numerical rhetoric and vote targets, the framing of political activities as “relaxed but structured,” and the acronym SSB (System, Strategy, Budget) as a technocratic justification for political mobilization. The study also demonstrates asymmetrical power relations between the City of Jayapura and the Provincial Government of Papua, strengthened by access to national political networks, external financial resources, and the co-optation of local elites in surrounding districts. The study concludes that language functions not merely as a medium of communication but as an ideological instrument for legitimizing political interests and reproducing power relations. These findings contribute to critical discourse studies and local political studies by revealing how bureaucratic authority, discourse, and political patronage intersect in contemporary electoral practices in Papua.